The failure of a tungsten carbide-cobalt cored projectile penetrating a hard target - Woolmore, Nicola J. (Engineering Systems Department, 2010)
Experimental results are presented from an investigation of the parameters of a ceramic-faced armour system that are required to induce damage in a tungsten carbide - cobalt (WC-Co) penetrator. A WC-Co material model has been successfully developed and implemented within the numerical hydrocode AUTODYN 2D. The understanding of penetration mechanisms was used to guide a parametric investigation, validating the WC-Co material failure model with experimental results. A series of experiments has been conducted firing the Russian 14.5 mm BS41 WC-Co cored projectile into various thicknesses and types of alumina (Al2O3) and silicon carbide (SiC), backed by aluminium alloy or mild steel semi-infinite witness blocks. Results demonstrated that SiC B out-performed standard monolithic armours and a selection of other armour ceramics including PS 5000 SiC and Sintox-CL. After comminution, the SiC B consisted of particles of closely interlocked grains. These appeared to provide considerable resistance to deviatoric stresses. Results suggest that it is not only increased hardness but also the nature of the fracture of the ceramic ahead of the penetrator that improves the armour’s ballistic performance at defeating WC-Co penetrators. If such superior ballistic response can be controlled and incorporated into practical armour systems, it will provide the basis for an advance in armour protective capability against WC-Co penetrators. In addition, a numerical material model derived from experimental data was developed to provide a preliminary tool to study the WC-Co failure. It was demonstrated that the numerical estimation of WC-Co behaviour using a shock Equation Of State (EOS), a piecewise linear strength model and a principle stress failure model provides a good method to estimate spall behaviour under dynamic loading in AUTODYN 2D. Successful numerical simulation of the material model used demonstrated the future potential of the technique.